Ranking Variables Affecting Efficiency of Insurance Companies by Using Fuzzy ANP - Nahid Feizabadi Farahani; mohammad ali dehghan dehnavi; Yahya Hassas Yeganeh; Meysam Amiri (مطالعات تجربی حسابداری مالی, 2019)
Given the high volume of insurance industry turnover, the role of the capital of insurance companies and their number in the stock exchange is very important. Since the investors' goal of investing in each company is to generate returns in line with their investment, if the company contributes to the creation of value, Success will benefit not only the homeowners of the company but also the wider community. The purpose of the present research is to evaluate the variables affecting the performance of insurance companies using the fuzzy ANP technique. The statistical population of this study includes all active members of insurance companies active in the stock exchange and OTC, as well as experts of Tehran Stock Exchange. In this research, we tried to select the majority of experts in the Insurance Organization and some of the managers of insurance companies, and the sample size is 35 people using the Cochran formula. After analyzing, using a specific fuzzy ANP technique Which ranked first in terms of capital productivity, then asset quality, liabilities, liquidity, management quality, market risk sensitivity, profitability, operational efficiency, and capital structure and capital adequacy